The Making of Ship Points and Lines Assisted by the C-MAP Application to Practice Students' Collaboration Skills - Rahmad Fauzan (Journal on Education, 2023)
One of the causes of accidents in the waters is the result of neglecting the point and the line of the ship. To indicate the presence of a ship using C-MAP, one way is to select a point using the save location in the navigator tools. Then when the ship starts sailing, immediately use the save track in the navigator tools to make a line. The minimum number of points that must be made is 5 pieces. The more places stored in a route, the neater the route will be. The method used is descriptive qualitative with data collected in the form of a display. Although this application can be used offline, it demands that the user is always present and only uses this application and not in conjunction with other applications on one device. It would be more suitable if there is more than one user using this app, working in a teams or taking turns.